A Pilot Study on Tocilizumab for Treating Refractory Adult-Onset Still's Disease. Issue 1 (December 2017) - Li, Ting; Gu, Liyang; Wang, Xiaodong; Guo, Li; Shi, Hui; Yang, Chengde; Chen, Sheng
Abstract To investigate the efficacy and safety of Tocilizumab (TCZ) in patients with refractory adult-onset Still's disease (AOSD). We enrolled 8 female patients from October 2013 to July 2014. All patients fulfilled Japan's Yamaguch AOSD classification and recognized as refractory AOSD. All Patients received TCZ treatment 4–8 mg/kg every 4 weeks. Evaluation of efficacy was conducted after 3 months and 6 months, including clinical manifestations of AOSD patients, improvement of inflammatory markers as well as glucocorticoids dosage adjustments. Treatment-related adverse events were also recorded. Patients treated with Tocilizumab with average age 41.1 years old, the average disease duration 23.6 months. Two patients drop off due to infusion side effects. Others were followed at least 6 months. After 3 months of follow-up, remission rates of fever, arthritis and rashes from 8 patients were 87.5%, 100% and 87.5%. White blood cell counts, erythrocyte sedimentation rate, C-reactive protein and ferritin levels were decreased (P < 0.01) significantly compared to treatment before. Furthermore, the average dose of prednisone was reduced from 51.7 ± 38.4 mg/d to 12.9 ± 7.7 mg/d (P < 0.01). Our findings suggest that tocilizumab could alleviate the clinical manifestations of refractory AOSD rapidly and efficiently.